Developing a Mobile Reading Comprehension Test for Junior High School Students by Using Ispring-Suite - Muttahida (Nusantara Science and Technology Proceedings, 2024)
Online assessment has been largely used by EFL teachers in assessing students’ reading comprehension skills. However, since not all schools are equipped with a good internet connection, a mobile test can be a solution. This paper aims to develop a mobile reading comprehension test for junior high school students by using iSpring-Suite. This mobile reading comprehension test can be used in online and offline settings. This paper employed a Research and Development (R&D) method which includes some stages, namely: Planning, Designing, and Development. The stages of test development were also designed using a criterion of the good test, such as practicality, validity, and reliability. The pilot testing was conducted in SMP N 1 Mauponggo Satap and twenty-four grade 8 students took the test. The teachers can directly set answer key and take the students’ score in using iSpring-Suite, so it was practical and effective to use. The validity score for all question items was between 0.6 and 0.8 which means that the items are in good categories or valid. Meanwhile, the realibility test result showed that the test items have a very high reliability with the Cronbarch Alpha value 0.613 or more than 0.6 which indicated that the items were reliable. It can be concluded that this mobile reading comprehension test has a high possibility to use. Due to its limitation, the next researcher can design the test with a larger scale with more participants to gain more valid and reliable result.